Pretreatment of Pennisetum sinese silages with ferulic acid esterase-producing lactic acid bacteria and cellulase at two dry matter contents: Fermentation characteristics, carbohydrates composition and enzymatic saccharification. (January 2020) - Li, Fuhou; Ke, Wencan; Ding, Zitong; Bai, Jie; Zhang, Yixin; Xu, Dongmei; Li, Ziqian; Guo, Xusheng
Highlights: First reported the application of FAE-producing LAB in P. sinese pretreatment. Lp A1 enhanced the degradation of lignocellulose, especially the ADL. Pretreatment with Lp A1 improved enzymatic digestibility regardless of DM content. Lp A1 performed better for cellulose convertibility in H-DM versus L-DM forages. Abstract: The impact of Lactobacillus plantarum A1 producing ferulic acid esterase and Acremonium cellulase on Pennisetum sinese silages was investigated at two dry matter contents by studying the ensiling characteristics, lignocellulosic degradation and enzymatic saccharification properties. The P. sinese was treated with nothing (control), Acremonium cellulase (AC), L. plantarum A1 (Lp) and AC + Lp and ensiled for 60 d. All additive treatments effectively preserved P. sinese and promoted the degradation of lignocellulose in comparison with control. Pretreatment with AC exhibited better effects in degradation of lignocellulose and enhancing enzymatic saccharification of P. sinese silage with low dry matter content (L-DM), while AC + Lp performed better in lignocellulose degradation in silages with high dry matter content (H-DM). Application of Lp exhibited a better performance in reducing the concentration of acid detergent lignin in treated silages. In addition, Lp enhanced enzymatic saccharification at 72 h in H-DM silage relative to other treatments.